2014
DOI: 10.2331/suisan.80.561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of removing Diadema on barren ground in Haidaura Bay, Mie Prefecture

Abstract: EŠects associated with removing the sea urchin Diadema spp. from an area of barren ground were examined in Haidaura Bay in Mie Prefecture, central Japan, from December 2009 to December 2012. Diadema spp. were harvested using scoop nets and spears from boats, or crushed by divers using metal rods. Three experimental areas in which initial Diadema spp. densities were high (8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…We previously reported that Diadema-dominated barren grounds in Haidaura Bay (Mie Prefecture, central Japan) transitioned seaweed beds after removing D. setosum and Diadema sp. (Kurashima et al 2014). Algal coverage in this area increased when Diadema density decreased to 2 ind.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…We previously reported that Diadema-dominated barren grounds in Haidaura Bay (Mie Prefecture, central Japan) transitioned seaweed beds after removing D. setosum and Diadema sp. (Kurashima et al 2014). Algal coverage in this area increased when Diadema density decreased to 2 ind.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, seaweed beds have recovered in barren ground areas as a result of removing Diadema spp. (Kurashima et al 2014). The present study was performed at the point marked study site in the inner area of Haidaura Bay (Fig.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The subsidence was estimated by comparing the pre-and postearthquake water depths. The substrate types within the quadrats were classified and recorded (Kurashima et al 2014).…”
Section: Methodsmentioning
confidence: 99%